Perspectives on the Therapeutic Benefits of Arginine Supplementation in Cancer Treatment - Beal, Fabiani L. R.; Beal, Pedro R.; Beal, Juliana R.; Carvalho-Neves, Natan; Franco, Octávio L.; Silva, Osmar N. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Arginine is considered a semi-essential amino acid in healthy adults and the elderly. This amino acid seems to improve the immune system, stimulate cell growth and differentiation, and increase endothelial permeability, among other effects. For those reasons, it has been theorized that arginine supplementation may be used as an adjuvant to conventional cancer therapy treatments. Objective: This review aims to evaluate the existing knowledge of the scientific community on arginine supplementation in order to improve the efficacy of current cancer treatment. Results: Despite the continued efforts of science to improve treatment strategies, cancer remains one of the greatest causes of death on the planet in adults and elderly people. Chemo and radiotherapy are still the most effective treatments but at the cost of significant side effects. Conclusion: Thus, new therapeutic perspectives have been studied in recent years, to be used in addition to traditional treatments or not, seeking to treat or even cure the various types of cancer with fewer side effects.
Keywords: cancer